1996
DOI: 10.1182/blood.v88.11.4265.bloodjournal88114265
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic T-cell lymphoma: a distinct clinicopathologic entity of cytotoxic gamma delta T-cell origin

Abstract: We identified eight cases of T-cell lymphoma with evidence of a gamma delta phenotype over a 13-year period. Seven of these cases conformed to a distinct clinicopathologic entity of hepatosplenic gamma delta T- cell lymphoma. Nearly all of these patients were young adult males (five of seven), with a median age at presentation of 20 years. They presented with marked hepatosplenomegaly, without lymphadenopathy or significant peripheral blood lymphocytosis. Thrombocytopenia was seen in all patients, and five of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(68 citation statements)
references
References 41 publications
(1 reference statement)
6
58
0
Order By: Relevance
“…29,30 We and others have already demonstrated that ␥␦ T-cell lymphomas are derived from cytotoxic ␥␦ T-cells. 18,23,31 These cells can be regarded as a first line of immunodefense in various mucosal and epithelial sites. 32 The absence of cytotoxic proteins in tumour cells of most of CD30 negative cutaneous T-cell lymphomas was also observed in mycosis fungoides and in Sezary syndrome, in which cells with a cytotoxic profile had the appearance of reactive lymphocytes 33,34 (personal data).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 We and others have already demonstrated that ␥␦ T-cell lymphomas are derived from cytotoxic ␥␦ T-cells. 18,23,31 These cells can be regarded as a first line of immunodefense in various mucosal and epithelial sites. 32 The absence of cytotoxic proteins in tumour cells of most of CD30 negative cutaneous T-cell lymphomas was also observed in mycosis fungoides and in Sezary syndrome, in which cells with a cytotoxic profile had the appearance of reactive lymphocytes 33,34 (personal data).…”
Section: Discussionmentioning
confidence: 99%
“…As there is no effective therapy for HSTCL, all cases were fatal. HSTCL is a rare clinicopathological entity, usually of cytotoxic, gd T-cell origin (53). Although the incidence of this disease is unknown, about 200 cases have been reported since its first description in 1981.…”
Section: Evidence From Case Reports and Case Seriesmentioning
confidence: 99%
“…1,2 Most postthymic neoplasms that arise from this ␥␦ T-cell subpopulation can be classified as hepatosplenic ␥␦ lymphomas. [3][4][5][6] On the other hand, only a few cases of non-hepatosplenic ␥␦ lymphoma have been reported. 7,8 Hepatosplenic ␥␦ T-cell lymphoma is a rare, recently described subset of peripheral T-cell lymphomas characterized by hepatosplenomegaly without lymphadenopathy, clinically significant cytopenia and an aggressive clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Hepatosplenic ␥␦ T-cell lymphoma is a rare, recently described subset of peripheral T-cell lymphomas characterized by hepatosplenomegaly without lymphadenopathy, clinically significant cytopenia and an aggressive clinical course. [3][4][5][6] These lymphomas preferentially infiltrate hepatic sinusoids and splenic red pulp but may also involve lymph node sinuses, bone marrow and peripheral blood. 5,6 Non-hepatosplenic ␥␦ T-cell lymphoma can be regarded as a model of lymphoma derived from activated cytotoxic cells, occurring in mucosa or skin.…”
Section: Introductionmentioning
confidence: 99%